2005
DOI: 10.1902/jop.2005.76.9.1431
|View full text |Cite
|
Sign up to set email alerts
|

A Long‐Term Study of Implants Supporting Overdentures as a Model for Implant Success

Abstract: 1) Survival of implants supporting overdentures was very high; 2) implants supporting overdentures in the maxilla had greater CBL than in the mandible; and 3) new criteria of implant success should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
2
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 12 publications
6
77
2
8
Order By: Relevance
“…Uribe et al [2005] reported survival rates of 90-100% for the lower jaw and 66-95.5% for the upper jaw. Similar results have been published by other authors [Cochran, 1999;Schwartz-Arad et al, 2005], and our results support these clinical findings. Pradel et al [2005] studied the proliferation and differentiation rates of human spongiose bone sludges versus those of bony chips of the corticalis both obtained from the maxilla or mandible.…”
Section: Discussionsupporting
confidence: 94%
“…Uribe et al [2005] reported survival rates of 90-100% for the lower jaw and 66-95.5% for the upper jaw. Similar results have been published by other authors [Cochran, 1999;Schwartz-Arad et al, 2005], and our results support these clinical findings. Pradel et al [2005] studied the proliferation and differentiation rates of human spongiose bone sludges versus those of bony chips of the corticalis both obtained from the maxilla or mandible.…”
Section: Discussionsupporting
confidence: 94%
“…Other studies have reported a higher rate of survival in the mandible compared to the maxilla 1,4,14 , and it may well be that failure to demonstrate this was due to the lower number in the mandible group. Interestingly, there was very little difference in implant survival in edentulous cases whether an onlay or osteoplasty technique was used.…”
Section: Discussionmentioning
confidence: 90%
“…Further, related outcomes could not be extracted from nine articles [11][12][13][14][15][16][17][18][19] , one article compared different implant systems and opposing dentition was not reported 20 . In one article 21 27 corresponding to (Visser et al 35 ), Batenburg et al 28 , and de Jong et al…”
Section: Results:-mentioning
confidence: 99%